Evaluation of Intravenous Diphenhydramine Use in Patients with Sickle Cell Vaso-Occlusive Crisis. (December 2021) - Rector, Katherine; Merchant, Shelby; Crawford, Rachel; Arnall, Justin R.; Symanowski, James; Veeramreddy, Padmaja; Osunkwo, Ifeyinwa
Purpose: To compare the incidence of oversedation between oral and parenteral diphenhydramine therapy for treatment of opioid-induced pruritus in patients with sickle cell disease vaso-occlusive crisis (SCD VOC).Methods: This retrospective, single-center, cohort study included patients greater than or equal to 18 years old with sickle cell disease admitted for vaso-occlusive crisis who received either intravenous or oral diphenhydramine for opioid-induced pruritus. Patients were identified through ICD-9 and ICD-10 codes from June 1, 2016 through July 1, 2017. Rates of oversedation were compared between the 2 formulations. Secondary endpoints included length of stay, amount and duration of diphenhydramine, rate of acute chest and indication for IV therapy.Results: Fifty unique patients were included in the analysis representing 121 admissions. Seven patients received both formulations on separate admissions and were included in both groups. Twenty-nine percent of patients in the IV diphenhydramine group experienced oversedation (12/42) versus 13% in the oral diphenhydramine group (2/15, P = .312). The average number of admissions was significantly higher in the IV versus oral group (2.45 vs 1.20; P = .005) with average and median length of stay also significantly higher in the IV versus oral group (30.57, 16.0 vs 10.67, 10.0; P = .003).Conclusion: While there was no statistically significant difference in the rates of oversedation with use of IV versus oral diphenhydramine formulations, patients with SCD VOC who received IV diphenhydramine had more frequent admissions and a longer length of stay. Clinicians may consider oral diphenhydramine preferentially in appropriate patients over IV administration.